El uso de la tecnología blockchain para desarrollar una cadena logística sostenible en el transporte marítimo internacional: caso peruano - Babilonia Martel, Paolo (2022)
The aim of this thesis is to analyze the impact of the use of blockchain technology in the development of a sustainable logistics chain in Peruvian international shipping. The research is carried out in a world scenario with projection to be increasingly globalized and connected through new information technologies. In view of this and thanks to the literature review, it has become evident that blockchain technology has a marked positive trend to be present in large businesses that need a real-time exchange of information with other members of the chain. Therefore, it was intended to test whether the use of blockchain technology in port logistics operators would influence their performance and efficiency. The study employs a qualitative analysis as fifteen in-depth interviews were conducted targeting managers and senior people working in the public and private sector. We focused on logistics operators with more than fifteen years of experience in foreign trade logistics with ISO certification and BASC regulation, and public institutions related to the sector, located in Metropolitan Lima. Thus, the results of the interviews corroborate that information storage, process automation, traceability, security in the logistics chain, competitiveness in logistics costs and transparency of information are influential variables in the activities carried out by logistics operators to have a good control of the entire logistics chain.